1993
DOI: 10.1590/s0373-55241993000100008
|View full text |Cite
|
Sign up to set email alerts
|

Salinity and temperature effects on the growth and chlorophyll-α content of some planktonic aigae

Abstract: • AbstTrlct: The eflect of salinity (0-40 %o) and temperature (l1-36"C, at S"C intervals)variations on maximum growth rate (div d-I ), maximum yield (10810 ccB number) and chlorophyl1-a content (pg celr l ) of four planktonic algae was examined under laboratory conditions. Phaeodactylum tricomutwn grew over the entire range of experimental salinities, at 11-26 °C. The highest maximum growth rates ( 1.6 div d-I) occurred between 9-300/00 and 16-26 "C. Optimum salinity range for maximum yield ChlorophyU-a conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 37 publications
3
8
0
Order By: Relevance
“…In agreement with this result, Karsten and Kirst (1989) pointed out that chlorophyll a content of Bostrychia radicans increased with the increment of salinity level. In contrast, Sigaud and Aidar (1993) showed that temperature and salinity did not have an influence on the chlorophyll-a content per cell for Phaeodactylum triconutum and Tetraselmis gracilis. These contradictions about the relation between chlorophyll a content and salinity level may be due to the difference of the studied algal taxa.…”
Section: Resultsmentioning
confidence: 74%
“…In agreement with this result, Karsten and Kirst (1989) pointed out that chlorophyll a content of Bostrychia radicans increased with the increment of salinity level. In contrast, Sigaud and Aidar (1993) showed that temperature and salinity did not have an influence on the chlorophyll-a content per cell for Phaeodactylum triconutum and Tetraselmis gracilis. These contradictions about the relation between chlorophyll a content and salinity level may be due to the difference of the studied algal taxa.…”
Section: Resultsmentioning
confidence: 74%
“…*, no data available or calculation impossible (LC <highest test concentration); "rst estimate; preliminary; test duration deviated; concentration expressed as total sul"de; age of the organisms di!ered. References: (1) ISO 11348, 1998; (2) Whale et al, 1998;(3) Bulich et al, 1981;(4) Qureshi et al, 1982;(5) van Leeuwen et al, 1985;(6) Sigaud and Aidar, 1993; (7) values are given. If no special notes are present concerning the temperature, the pH, or the salinity, experiments (e.g., concerning toxicity of ammonia) were performed using the standard experimental temperature, pH, and salinity.…”
Section: Resultsmentioning
confidence: 99%
“…In such cases, separate criteria should probably be speci"ed concerning both factors. For example, the algae Phaeodactylum tricornutum might survive and grow well in the range between 4 and 32 (Sigaud and Aidar, 1993), but the maximum di!erence in salinity between the inoculum and test conditions should be limited to circa 6 to 8 (unpublished data AquaSense). Chloride or salinity tests involving freshwater organisms were performed without prior acclimation of the organisms to increased values.…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that under elevated temperature, the metabolism of O. tauri was increased, leading the cells to synthesise more chlorophyll. Temperature did not affect chlorophyll a content in diatoms (Sigaud and Aidar, ). Salinity appears to affect different phytoplankton species differently, with some species showing no change in chlorophyll content across a range of salinities, and others having higher chlorophyll contents at the optimum salinity for growth (McLachlan, ; Sigaud and Aidar, ).…”
Section: Discussionmentioning
confidence: 99%